Medical simulation as an educational tool in the opinion of nursing students - Tomaszewska, Katarzyna (Nursing in the 21st Century, 2022)
TO MEDICAL SIMULATION AS AN EDUCATIONAL TOOL IN THE OPINION OF NURSING STUDENTSOL IN THE OPINION OF NURSING STUDENTSIntroduction. Nursing education combined with medical simulation is currently a modern method of education, which, especially in the era of the SARS-COV-2 pandemic, is an essential form of preparing the student for professional tasks.Aim. The aim of the study was to fi nd out the opinions of nursing students about the classes conducted in the Medical Simulation Center.Material and methods. A total of 186 undergraduate nursing students participated in the survey. It was conducted via the Internet. We used the method of diagnostic survey; surveying technique and the tool was the original questionnaire. The study was anonymous and voluntary and was conducted from February to May 2021. It is assumed that any relationship is statistically signifi cant when p≤0.05.Results and conclusions. According to the respondents, medical simulation prepares to acquire practical skills, also consolidates theoretical knowledge, prepares to broaden social competence. For nursing students, its disadvantage is the lack of contact with the patient. Education realized with the use of medical simulation is an eff ective method of learning. Nursing students prefer to take classes in high fi delity rooms and with standardized patients because they are most similar to real life conditions.